Peran Pendidikan Akhlak dalam Membentuk Karakter Berbakti Anak Kepada Orang Tua - Afikah Al-Aliyah; Irda Fauziah; Siti Masyithoh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Moral education is the main pillar in shaping the character of children who have integrity, empathy, and have high moral awareness, especially in terms of filial devotion to parents. In the midst of the advancement of the times and the rapid development of technology, children face great challenges in maintaining noble moral values. The unstoppable flow of digital information often presents content that is contrary to family and religious values. Therefore, moral education is present as a systematic effort to instill good values in a sustainable and contextual manner with the development of the times. This study uses a library research approach to explore the role of moral education in shaping the character of children who are devoted to their parents. Data sources are collected from scientific journals, textbooks, and current academic articles relevant to the theme. The results of the study show that the formation of filial character is greatly influenced by the example of parents and teachers, habituation of positive behaviors such as good manners, worship together, and affectionate communication. In addition, the integration of moral values in the school environment, explicit curriculum policy support for character education, and the wise use of digital media are important factors in supporting the success of moral education. Furthermore, strengthening the school culture and the active involvement of the community in internalizing moral values also strengthen the moral education process. This study concludes that moral education cannot run in isolation, but must be the result of synergy between family, school, and community. Thus, children not only grow up as intellectually intelligent individuals, but also have emotional and spiritual intelligence that reflects an attitude of respect and love for parents. Strong moral education from an early age is a long-term investment for the formation of a generation with noble character.